Studi Kasus Penyebab Kecelakaan Kerja Fatal di Tambang Mineral: Analisis Faktor Manusia, Teknis, dan Lingkungan - Gatan Abdillah; Muhammad Krisna Caraka; Rezano Ahmad Arioyudanto; Siroj Ahya; Denny Oktavina Radianto (Lembaga Pengembangan Kinerja Dosen, 2024)
Fatal occupational accidents in the mineral mining industry are a crucial issue that requires special attention. This research aims to analyze in-depth the factors causing fatal occupational accidents in mineral mines using a case study approach. Through detailed investigation of a specific fatal occupational accident incident, this research explores the roles of human, technical, and environmental factors that contribute to the occurrence of the accident. By uncovering the complexity of interactions among these factors, this research is expected to provide valuable insights for the mineral mining industry in efforts to improve occupational safety and health, as well as to prevent the recurrence of similar tragedies in the future.